Viabilidade zootécnica e econômica do baraço de batata-doce em dietas para coelhos de corte - Klinger, Ana Carolina Kohlrausch (2019)
This study aimed to evaluate the use of sweet potato vines (BBD) in diets for growing rabbits. In order to reach the aim, two biological trials were developed, with different levels of BBD as a substitute to alfafa hay. A completely randomized experimental design was used. New Zealanad rabbits by the initial age of 35 days and final age of 77 days were used in the first trial, and, in the second trial, by the final age of 84 days. In the first biological trial, there were three dietary groups: control diet, with conventional ingredients; a diet with 50% replacement of alfafa hay by BBD (50 BBD) and another with 100% (100BBD) of alfafa hay replacement by BBD. The second trial presented five dietary groups: a control diet, similar to the first trial; the four others followed levels of 25% (25BBD), 50% (50BBD), 75% (75BBD) and 100% (100BBD) of alfafa hay replacement by BBD. In both trials, each diet was used to feed 10 animals. The variables evaluated were performance, carcass characteristics, meat composition and metabolic parameters, hepatic metabolism, blood metabolism, intestine morphology, digestive enzymes and fur. Data were evaluated and statistically compared by Analysis of Variance followed by Tukey test (p<0,05). Regression analysis was used in the second trial. Subsequently, an economical study was developed, based on total operating costs and economic feasibility of each trial. It was possible to verify that BBD did not influence in performance variables. However, as alfafa hay was replaced by BBD, daily feed intake and mass gain tended to reduce. Feed conversion data were identical in all treatments, in both trials. Triglycerides and cholesterol decreases caused by the ingredient are highlighted, while HDL-cholesterol, glucose, blood protein and alanine aminotransferase were stable. With regard to hepatic variables result, the liver mass decreased according to the increase of alfafa hay replacement, which can be explained by glucose concentration in liver tissue. BBD caused reduction in chymotrypsin production and increased the presence of protein in the intestine. Performance parameters, specially feed conversion, and production cost lead to conclude that BBD may be a substitute to alfafa hay in diets for rabbits. It is suggested that future studies consider a shorter time between crop and plantation as that could reduce some antinutritional factors observed in this study.